Association between Handedness, Grip Strength and Writing-Speed Among Young Undergraduates in South-West, Nigeria - Desmond, Zaki A.; Mahmud, Karaga A.; Precious, Onyenweaku C.; Jeremiah, Owolabi A.; Omotayo, Tabiti O.; David, Farounbi A.; Muhammad, Dan I. A. (Darul Yasin Al Sys, 2025)
Background: Writing-speed plays a crucial role in various academic and professional disciplines and it is an unavoidable part of students’ activities. Previous studies have explored different factors that influence writing-speed among students, However, there is dearth of literature on the role of handedness and grip strength on writing-speed among this population. Aims: To investigate the association among each of handedness, grip strength and writing-speed. Methods: 368 undergraduates of Bowen University, were recruited into this cross-sectional study using consecutive sampling technique. Mean, frequency, percentages and pie charts were used to describe the data; Mann-Whitney U, Spearman rank correlation and Chi-square test was used for inferential analysis at alpha level set at 0.05. Results: Mean age of participants’ 20±2 years and most of the participants were right handed (77.7%). There was significant relationship (p=0.00) between age and grip strength. There was no significant relationship between age (p=0.164) and writing-speed and between grip strength (p=0.108) and writing-speed. While there were no significant differences between grip strength (p=0.062) or writing-speed (p=0.116) and handedness, significant differences were found between gender and both grip strength (p=0.025) and writing-speed (p=0.00). There was significant association (p=0.00) between handedness and gender. Conclusion: The study found that males had stronger grip strength and faster writing speeds than females, likely due to physiological differences and varying social experiences. Handedness did not significantly impact grip strength or writing speed, suggesting other factors like practice are more influential. Age correlated positively with grip strength but did not affect writing speed, likely due to muscle development. The association between gender and handedness may reflect both biological and cultural influences. These findings highlight the importance of considering gender and age in motor skills research.